2014
DOI: 10.1111/bju.12581
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dyslipidaemia in patients with renal cell carcinoma: a case‐control study in China

Abstract: ObjectiveTo examine the prevalence of dyslipidaemia in patients with renal cell carcinoma (RCC) in a Chinese population. Patients and MethodsIn all, 550 histologically confirmed RCC cases and 570 controls, matched for age and sex were included. Total cholesterol, triglyceride, low-density lipoprotein (LDL) and high-density lipoprotein (HDL) were assessed before treatment using standard techniques. The lipid profiles were defined as 'normal' , 'borderline high' , 'high' and 'low' according to Chinese Guidelines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Their finding did not apply to patients with genetically reduced LDL cholesterol levels, which implies that low LDL cholesterol levels per se do not cause cancer. In contrast, a retrospective case–control study of patients with newly diagnosed sporadic RCC [ 88 ] reported an upward trend for the occurrence of advanced RCC with rising serum LDL levels. Elevated levels of LDL also frequently co-existed with the presence of clear-cell RCC.…”
Section: Dyslipidemiamentioning
confidence: 97%
See 1 more Smart Citation
“…Their finding did not apply to patients with genetically reduced LDL cholesterol levels, which implies that low LDL cholesterol levels per se do not cause cancer. In contrast, a retrospective case–control study of patients with newly diagnosed sporadic RCC [ 88 ] reported an upward trend for the occurrence of advanced RCC with rising serum LDL levels. Elevated levels of LDL also frequently co-existed with the presence of clear-cell RCC.…”
Section: Dyslipidemiamentioning
confidence: 97%
“…Lipid disorders have been suggested to be involved in the pathomechanisms of various cancers, including oesophageal, colon, rectal, and renal cancers [ 86 , 87 ]. According to numerous studies, clear-cell renal cancer is also characterized by sterol storage in tumour cells resulting in alterations in lipid metabolism and consequently, in the formation and progression of RCC [ 1 , 88 ]. However, the exact mechanisms are not fully understood as the results of studies are sometimes conflicting.…”
Section: Dyslipidemiamentioning
confidence: 99%
“…The role of dyslipidemia as a risk factor for kidney cancer is unclear and has been suggested by many studies. A study by Zhang et al21 in China showed that high low-density lipoprotein (LDL) levels were frequent among kidney cancer patients and most common in those with clear cell kidney cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al. recently showed in a case‐control study of Chinese subjects that abnormal LDL elevation is prevalent in patients with RCC. Although lipoprotein fractions were not available for the present study, they merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…low-density lipoprotein (LDL) or high-density lipoprotein impact the activity of Akt, mitogen-activated protein kinase (MAPK), extracellular signal-regulated kinase (ERK)1/2 and Signal Transducer and Activator of Transcription 3 (STAT3) pathways and subsequently tumour proliferation, migration and invasion [23]. Zhang et al [24] recently showed in a case-control study of Chinese subjects that abnormal LDL elevation is prevalent in patients with RCC. Although We did not find a difference in cholesterol levels between the three major RCC subtypes.…”
Section: Discussionmentioning
confidence: 99%